Sample Size Implications of Multi-Day GPS-Enabled Household Travel Surveys - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
TRB's National Cooperative Highway Research Program (NCHRP) Research Results Digest 400: Sample Size Implications of Multi-Day GPS-Enabled Household Travel Surveys summarizes an NCHRP project that studied the design of household travel surveys. Multi-day travel surveys are now more feasible, given global positioning system (GPS) technology. This project explores if surveys using a GPS device provides less drop-off in response compared to travel diaries. This project also investigates the effects of using multi-day data for developing travel demand models and explores the impact of sample size on multi-day versus single-day surveys.Appendixes A through J are available online.
Keywords: Transportation and Infrastructure

Assessment in Support of Instruction and Learning: Bridging the Gap Between Large-Scale and Classroom Assessment: Workshop Report - National Research Council (The National Academies Press, 2003)
Assessment in Support of Instruction and Learning is the summary of a National Research Council workshop convened to examine the gap between external and classroom assessment. This report discusses issues associated with designing an assessment system that meets the demands of public accountability and, at the same time, improves the quality of the education that students receive day by day. This report focuses on assessment that addresses both accountability and learning.
Keywords: Education

Development Planning: A Strategic Approach to Future Air Force Capabilities - National Research Council (The National Academies Press, 2014)
The development and application of technology has been an essential part of U.S. airpower, leading to a century of air supremacy. But that developmental path has rarely been straight, and it has never been smooth. Only the extraordinary efforts of exceptional leadership - in the Air Forces and the wider Department of Defense, in science and in industry - have made the triumphs of military airpower possible. Development Planning provides recommendations to improve development planning for near-term acquisition projects, concepts not quite ready for acquisition, corporate strategic plans, and training of acquisition personnel. This report reviews past uses of development planning by the Air Force, and offers an organizational construct that will help the Air Force across its core functions. Developmental planning, used properly by experienced practitioners, can provide the Air Force leadership with a tool to answer the critical question, Over the next 20 years in 5-year increments, what capability gaps will the Air Force have that must be filled? Development planning will also provide for development of the workforce skills needed to think strategically and to defectively define and close the capability gap. This report describes what development planning could be and should be for the Air Force.
Keywords: Conflict and Security Issues

Air Cargo Facility Planning and Development—Final Report - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2015)
TRB’s Airport Cooperative Research Program (ACRP) Web-Only Document 24: Air Cargo Facility Planning and Development—Final Report reviews the process and information used in preparing ACRP Report 143: Guidebook for Air Cargo Facility Planning and Development. The guidebook explores tools and techniques for sizing air cargo facilities, including data and updated metrics for forecasting future facility requirements as a function of changing market and economic conditions.
Keywords: Transportation and Infrastructure

Leveraging Big Data to Improve Traffic Incident Management - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
"Big data" is not new, but applications in the field of transportation are more recent, having occurred within the past few years, and include applications in the areas of planning, parking, trucking, public transportation, operations, ITS, and other more niche areas. A significant gap exists between the current state of the practice in big data analytics (such as image recognition and graph analytics) and the state of DOT applications of data for traffic incident management (TIM) (such as the manual use of Waze data for incident detection).The term big data represents a fundamental change in what data is collected and how it is collected, analyzed, and used to uncover trends and relationships. The ability to merge multiple, diverse, and comprehensive datasets and then mine the data to uncover or derive useful information on heretofore unknown or unanticipated trends and relationships could provide significant opportunities to advance the state of the practice in TIM policies, strategies, practices, and resource management.NCHRP (National Cooperative Highway Research Program) Report 904: Leveraging Big Data to Improve Traffic Incident Management illuminates big data concepts, applications, and analyses; describes current and emerging sources of data that could improve TIM; describes potential opportunities for TIM agencies to leverage big data; identifies potential challenges associated with the use of big data; and develops guidelines to help advance the state of the practice for TIM agencies.
Keywords: Transportation and Infrastructure

Zero-Sustainment Aircraft for the U.S. Air Force: A Workshop Summary - National Research Council (The National Academies Press, 2013)
Overall Air Force weapon system sustainment (WSS) costs are growing at more than 4 percent per year, while budgets have remained essentially flat. The cost growth is due partly to aging of the aircraft fleet, and partly to the cost of supporting higher-performance aircraft and new capabilities provided by more complex and sophisticated systems, such as the latest intelligence, surveillance, and reconnaissance (ISR) platforms. Furthermore, the expectation for the foreseeable future is that sustainment budgets are likely to decrease, so that the gap between budgets and sustainment needs will likely continue to grow wider. Most observers accept that the Air Force will have to adopt new approaches to WSS if it is going to address this problem and remain capable of carrying out its missions. In this context, the original intent of this 3-day workshop was to focus on ways that science and technology (S&T) could help the Air Force reduce sustainment costs. However, as the workshop evolved, the discussions focused more and more on Air Force leadership, management authority, and culture as the more critical factors that need to change in order to solve sustainment problems. Many participants felt that while S&T investments could certainly help—particularly if applied in the early stages ("to the left") of the product life cycle—adopting a transformational management approach that defines the user-driven goals of the enterprise, empowers people to achieve them, and holds them accountable, down to the shop level. Several workshop participants urged Air Force leaders to start the process now, even though it will take years to percolate down through the entire organization. These sustainment concerns are not new and have been studied extensively, including recent reports from the National Research Council's Air Force Studies Board and the Air Force Scientific Advisory Board.
Keywords: Conflict and Security Issues; Space and Aeronautics

The Role of Experimentation Campaigns in the Air Force Innovation Life Cycle - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
The Air Force (USAF) has continuously sought to improve the speed with which it develops new capabilities to accomplish its various missions in air, space, and cyberspace. Historically, innovation has been a key part of USAF strategy, and operating within an adversary's OODA loop (observe, orient, decide, act) is part of Air Force DNA. This includes the ability to deploy technological innovations faster than do our adversaries. The Air Force faces adversaries with the potential to operate within the USAF's OODA loop, and some of these adversaries are already deploying innovations faster than the USAF. The Role of Experimentation Campaigns in the Air Force Innovation Life Cycle examines the current state of innovation and experimentation in the Air Force and best practices in innovation and experimentation in industry and other government agencies. This report also explores organizational changes needed to eliminate the barriers that deter innovation and experimentation and makes recommendations for the successful implementation of robust innovation and experimentation by the Air Force.
Keywords: Conflict and Security Issues

Greenhouse Gas Emissions Information for Decision Making: A Framework Going Forward - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
Climate change, driven by increases in human-produced greenhouse gases and particles (collectively referred to as GHGs), is the most serious environmental issue facing society. The need to reduce GHGs has become urgent as heat waves, heavy rain events, and other impacts of climate change have become more frequent and severe. Since the Paris Agreement was adopted in 2015, more than 136 countries, accounting for about 80% of total global GHG emissions, have committed to achieving net-zero emissions by 2050. A growing number of cities, regional governments, and industries have also made pledges to reduce emissions. Providing decision makers with useful, accurate, and trusted GHG emissions information is a crucial part of this effort. This report examines existing and emerging approaches used to generate and evaluate GHG emissions information at global to local scales. The report develops a framework for evaluating GHG emissions information to support and guide policy makers about its use in decision making. The framework identifies six criteria or pillars that can be used to evaluate and improve GHG emissions information: usability and timeliness, information transparency, evaluation and validation, completeness, inclusivity, and communication. The report recommends creating a coordinated repository or clearinghouse to operationalize the six pillars, for example, by providing timely, transparent, traceable information; standardized data formats; and governance mechanisms that are coordinated, trusted, and inclusive of the global community.
Keywords: Environment and Environmental Studies

Greenhouse Gas Emissions from Wildland Fires: Toward Improved Monitoring, Modeling, and Management: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
Climate change is fundamentally changing ecosystems and their fire conditions, and the 2023 fire season highlighted the urgency of developing and implementing solutions to address wildland fires. Wildland fires transfer carbon between the land and the atmosphere through emissions of greenhouse gases (GHGs), along with other gasses and particles. Though fires can be a natural part of healthy, evolving ecosystems, large, uncontrolled wildland fires can have devastating consequences to human health, communities, and biodiversity. Human-driven changes in wildland fire regimes have the potential to increase GHG emissions at a scale that could inhibit global efforts to achieve net-zero GHG emissions in the coming decades. The National Academies of Sciences, Engineering, and Medicine convened a workshop on September 13-15, 2023, to identify opportunities to improve measurements and model projections of GHG emissions from wildland fires and discuss management practices that could be incorporated into current and future action plans. Participants emphasized the importance of learning from historic and current Indigenous fire management practices and centering Indigenous voices and leadership across all stages of fire management. Different global ecosystems - particularly temperate, boreal, and tropical biomes - have been impacted by climate and land use changes where historical fire regimes and the carbon balance have been disrupted. However, discussions highlighted the diverse set of available regionally differentiated and ecosystem-appropriate mitigation strategies. With improved understanding of fires and their GHG emissions, better information for mitigation and management, and incorporation of wildfire GHG emissions into national accounting mechanisms, practitioners, communities, and decision makers will be better equipped to prepare, adapt, and respond to future wildland fires.
Keywords: Environment and Environmental Studies; Earth Sciences

Applying Big Data to Address the Social Determinants of Health in Oncology: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
The National Academies of Sciences, Engineering, and Medicine held the workshop Applying Big Data to Address the Social Determinants of Health in Oncology on October 28–29, 2019, in Washington, DC. This workshop examined social determinants of health (SDOH) in the context of cancer, and considered opportunities to effectively leverage big data to improve health equity and reduce disparities. The workshop featured presentations and discussion by experts in technology, oncology, and SDOH, as well as representatives from government, industry, academia, and health care systems. This publication summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine; Surveys and Statistics

State of the Industry Report on Air Quality Emissions from Sustainable Alternative Jet Fuels - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
TRB's Airport Cooperative Research Program (ACRP) Web-Only Document 35: State of the Industry Report on Air Quality Emissions from Sustainable Alternative Jet Fuels captures the current status of knowledge to reduce carbon dioxide emissions using sustainable alternative jet fuels (SAJF). In the process of reducing SAJF, emissions of other pollutants may also be reduced, which could be significantly beneficial to airports. These reductions are not yet well defined, leaving airports unable to realize what may be substantial benefits. The research team analyzed the published technical literature to validate that SAJF use reduces air pollutant emissions and does not cause any air pollutant emissions to increase.
Keywords: Transportation and Infrastructure

Airport Air Quality Management 101 - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
TRB's Airport Cooperative Research Program (ACRP) Research Report 185: Airport Air Quality Management 101 introduces airport employees who are not environmental specialists to airport air quality issues. Airport air quality management is highly complex and technical, with many different stakeholders, including the local community and local, state, and federal regulators.Larger airports have dedicated environmental experts; however, at most airports, environmental management is carried out by employees who are engaged in other aspects of airport operations or provide oversight of external environmental consultants who are executing the work.This report is accompanied by ACRP WebResource 4: Airport Air Quality Resource Library.
Keywords: Transportation and Infrastructure

Model Mutual Aid Agreements for Airports - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2013)
TRB’s Airport Cooperative Research Program (ACRP) Synthesis 45: Model Mutual Aid Agreements for Airports presents information on mutual aid agreements, addressing nearly every type of emergency that could affect airports and require outside resources. The report is designed to assist airport operators in creating and sustaining effective emergency management mutual aid partnerships by documenting the specifics of existing agreements.
Keywords: Transportation and Infrastructure

Report Series: Committee on Biological and Physical Sciences in Space: Using Commercial Lunar Payload Services (CLPS) to Achieve Lunar Biological and Physical Science Objectives: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
After several decades since the last human visit, NASA is planning to return to the Moon, this time not only to visit but also to carry out extensive scientific experiments, establish a habitat occupied by astronauts, and learn lessons that will help in preparations for the eventual establishment of a human presence on Mars. The Commercial Lunar Payload Services (CLPS) program, overseen by NASA, will provide transport to the Moon for scientists who want to carry out research on the lunar surface or in orbit around the Moon. Recognizing the need to introduce and explain the CLPS program to researchers, the Committee on Biological and Physical Sciences in Space of the National Academies of Sciences, Engineering, and Medicine held a workshop on March 24-25, 2021 entitled "Using Commercial Lunar Payload Services (CLPS) to Achieve Lunar Biological and Physical Science Objectives". The organization of the workshop was guided by the following question: Looking at the period of time prior to the release of the next decadal survey, how can this community support and utilize CLPS to address areas of research? This workshop proceedings summarizes the presentations and discussions from the workshop sessions.
Keywords: Space and Aeronautics

Aircraft and Airport-Related Hazardous Air Pollutants: Research Needs and Analysis - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2008)
TRB’s Airport Cooperative Research Program (ACRP) Report 7: Aircraft and Airport-Related Hazardous Air Pollutants: Research Needs and Analysis examines the state of the latest research on aviation-related hazardous air pollutants emissions and explores knowledge gaps that existing research has not yet bridged.
Keywords: Transportation and Infrastructure

Mental, Neurological, and Substance Use Disorders in Sub-Saharan Africa: Reducing the Treatment Gap, Improving Quality of Care: Summary of a Joint Workshop by the Institute of Medicine and the Uganda National Academy of Sciences - Institute of Medicine (The National Academies Press, 2010)
Millions of people in sub-Saharan Africa suffer from mental, neurological, and substance use (MNS) disorders, and most do not have the resources to obtain treatment. The Uganda National Academy of Sciences and the Institute of Medicine hosted a workshop to discuss the state of care for MNS disorders in sub-Saharan Africa.
Keywords: Health and Medicine

Proposed Practice for Alternative Bidding of Highway Drainage Systems - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2015)
TRB’s National Cooperative Highway Research Program (NCHRP) Report 801: Proposed Practice for Alternative Bidding of Highway Drainage Systems explores the application of a performance-based process for selection of drainage pipe systems. The selection process is based on satisfying performance criteria for the drainage system while considering the full range of suitable pipe materials.
Keywords: Transportation and Infrastructure

Incorporating Greenhouse Gas Emissions into the Collaborative Decision-Making Process - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2012)
TRB’s second Strategic Highway Research Program (SHRP 2) Report S2-C09-RR-1: Incorporating Greenhouse Gas Emissions into the Collaborative Decision-Making Process identifies where and how greenhouse gas (GHG) emissions and energy consumption fit into a conceptual decision-making framework, including key decision points.The report presents background information on the role of GHG emissions in the transportation sector, factors influencing the future of emissions, GHG emissions reduction strategies, as well as information on cost effectiveness and feasibility of these reduction strategies. It also presents case studies to illustrate different scales and institutional contexts for GHG analyses.A web-based technical framework, Integrating Greenhouse Gas into Transportation Planning, which was developed as part of SHRP 2 Capacity Project C09, provides information on the models, data sources, and methods that can be used to conduct GHG emissions analysis. The framework is part of the Transportation for Communities: Advancing Projects through Partnerships (TCAPP) website. TCAPP is organized around decision points in the planning, programming, environmental review, and permitting processes. TCAPP is now known as PlanWorks.SHRP 2 Capacity Project C09 also produced a Practitioners Guide that presents information on how GHG emissions can be incorporated into transportation planning when using different types of collaborative decision-making approaches and includes an appendix with detailed technical information for GHG analyses.An e-book version of this report is available for purchase at Amazon, Google, and iTunes.In June 2013, SHRP 2 released a project brief on SHRP 2 Project C09.
Keywords: Transportation and Infrastructure

Clearing the Air: Asthma and Indoor Air Exposures - Institute of Medicine (The National Academies Press, 2000)
Since about 1980, asthma prevalence and asthma-related hospitalizations and deaths have increased substantially, especially among children. Of particular concern is the high mortality rate among African Americans with asthma. Recent studies have suggested that indoor exposures—to dust mites, cockroaches, mold, pet dander, tobacco smoke, and other biological and chemical pollutants—may influence the disease course of asthma. To ensure an appropriate response, public health and education officials have sought a science-based assessment of asthma and its relationship to indoor air exposures. Clearing the Air meets this need. This book examines how indoor pollutants contribute to asthma—its causation, prevalence, triggering, and severity. The committee discusses asthma among the general population and in sensitive subpopulations including children, low-income individuals, and urban residents. Based on the most current findings, the book also evaluates the scientific basis for mitigating the effects of indoor air pollutants implicated in asthma. The committee identifies priorities for public health policy, public education outreach, preventive intervention, and further research.
Keywords: Environment and Environmental Studies; Health and Medicine

Reducing Fuel Consumption and Greenhouse Gas Emissions of Medium- and Heavy-Duty Vehicles, Phase Two: Final Report - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
Medium- and heavy-duty trucks, motor coaches, and transit buses - collectively, "medium- and heavy-duty vehicles", or MHDVs - are used in every sector of the economy. The fuel consumption and greenhouse gas emissions of MHDVs have become a focus of legislative and regulatory action in the past few years. This study is a follow-on to the National Research Council's 2010 report, Technologies and Approaches to Reducing the Fuel Consumption of Medium-and Heavy-Duty Vehicles. That report provided a series of findings and recommendations on the development of regulations for reducing fuel consumption of MHDVs. On September 15, 2011, NHTSA and EPA finalized joint Phase I rules to establish a comprehensive Heavy-Duty National Program to reduce greenhouse gas emissions and fuel consumption for on-road medium- and heavy-duty vehicles. As NHTSA and EPA began working on a second round of standards, the National Academies issued another report, Reducing the Fuel Consumption and Greenhouse Gas Emissions of Medium- and Heavy-Duty Vehicles, Phase Two: First Report, providing recommendations for the Phase II standards. This third and final report focuses on a possible third phase of regulations to be promulgated by these agencies in the next decade.
Keywords: Environment and Environmental Studies; Transportation and Infrastructure